The protective effect of different extracts of aerial parts of Artemisia ciniformis against H2O2-induced oxidative stress and apoptosis in PC12 pheochromocytoma cells - Leila Hosseinzadeh, Somayeh Mirzaei, Marziyeh Hajialyani, Farahnaz Ahmadi, Seyed Ahmad Emami, Mahdi Mojarrab (Journal of Applied Pharmaceutical Science, 2019)
The major objective of this study is to investigate whether Artemisia ciniformis (A. ciniformis) is able to rescue the PC12 neuronal cells from H2O2-mediated oxidative stress. Different antioxidant and apoptotic assays were conducted on A. ciniformis. Among different A. ciniformis extracts, three (petroleum ether, dichloromethane, and ethylacetate) were the most proper ones. The protective effects of these extracts against H2O2-induced cytotoxicity were examined. Ethyl acetate (EA) extract was fractionated and total phenolic and flavonoid contents (TPC and TFC) of fractions were estimated. EA extract was found to be the most effective extract on suppressing the toxicity of H2O2. It caused up to 35% reduction in H2O2-induced cellular death, more than 70% decrease in reactive oxygen species (ROS) accumulation, 47% increase in SOD activity, almost 175% decrease in caspase-3 activity, and more than 27% elevation in mitochondrial membrane potential level. After fractionation, the most potent fraction (F3) was found active in protecting PC12 cells from oxidative stress consequences. This fraction possessed the highest ratio of flavonoid to non-flavonoid phenolic compounds (TFC = 125.03 ± 1.31 mg quercetin equivalent/g and TPC = 127.18 ± 6.00 mg gallic acid equivalent/g), suppressed the toxicity mediated by H2O2 and successfully inhibited the overproduction of ROS caused by H2O2. These results altogether suggested A. ciniformis is a potential choice for preventing different neurodegenerative diseases.
Keywords: Artemisia ciniformis, neuroprotection, oxidative stress, PC12, medicinal plant.